Bony birth‐canal dimensions and obstetric constraints in hominoids. Issue 3 (18th November 2022) - Laudicina, Natalie M.; Cartmill, Matt
Abstract: Objectives: Comparative studies of the birth process in humans and other primates have focused on the pelvic inlet. This is a region of birth‐canal constraint in humans, but not in other primates. Thus, the true obstetric differences between humans and other apes remain unknown. This research seeks to document nonhuman ape birth‐canal morphologies and their relationships to critical dimensions of neonates, in order to determine what aspects of human birth are unique. Materials and Methods: Computer‐generated images of the scanned pelves of six extant hominoid species are used to compare entire birth canals as three‐dimensional entities, documenting and analyzing the functionally relevant metrics of the maternal pelvis and the obstetric constraints for each species. Results: The inlet is a poor basis of comparison for evaluating tightness of fit in nonhuman primates, whose birth canal is most constricted at the lower end of the sacrum. Previous studies have overestimated the capaciousness of the nonhuman hominoid birth canal (which appears to be just as tight a fit for the fetal head in hylobatids as it is in Homo sapiens ) and also misrepresented it as a simple straight tube. In fact, its cross‐sectional shape changes markedly from inlet to outlet in most hominoids. Conclusion: Nonhuman hominoids exhibit obstetric constraints unlike those seen in modern humans. Human adaptations to maternal‐fetal craniopelvic disproportion are unique owing to the constraints imposed by bipedality, and probably predate the origins of the genus Homo . Abstract : Reconstruction of an orangutan birth canal.